DEFECTIVE PHAGE AND CHROMOSOME MOBILIZATION IN Pseudomonas putida - Chakrabarty, A. M. (1969)
The transfer of transducing phage DNA in association with the mandelate genetic region of Pseudomonas putida strain PRS1 (termed pfdm) has been achieved by growing together mandelate-positive PpG2 cells harboring pfdm as an extrachromosomal element and mandelate-deleted PpG1 strains. This transfer is analogous to sexual conjugation in the enterobacteria. The transfer of pfdm elements is always associated with chromosome mobilization and some rare recombinants acquire genetic donor ability. We have therefore concluded that the pfdm elements are responsible for initiation of chromosome mobilization in a manner not yet fully understood.